How Can We Best Reduce Pain Catastrophizing in Adults With Chronic Noncancer Pain? A Systematic Review and Meta-Analysis - Schütze, R.; Rees, Clare; Smith, Anne; Slater, Helen; Campbell, J.; O'Sullivan, Peter (Churchill Livingstone, 2017)
© 2017 The American Pain Society. Pain catastrophizing (PC), defined as an exaggerated negative cognitive-affective orientation toward pain, is one of the strongest psychological predictors of pain outcomes. Although regularly included as a process variable in clinical trials, there have been no comprehensive reviews of how it can be modified. Using a registered protocol (PROSPERO 2016 CRD42016042761), we searched MEDLINE, PsychINFO, EMBASE, CINAHL, and CENTRAL up to November 2016 for all randomized controlled trials measuring PC in adults with chronic noncancer pain. Two authors independently screened studies and assessed bias risk using the Cochrane tool. Quality of evidence was rated according to Grading of Recommendations Assessment, Development and Evaluation criteria. We included 79 studies (n = 9,914), which mostly recruited participants with musculoskeletal pain and had low risk of bias. Meta-analyses (standardized mean difference) showed 9 interventions had efficacy compared with waitlist/usual care or active control, although evidence quality was often low. The best evidence (moderate-high quality) was found for cognitive-behavioral therapy, multimodal treatment, and acceptance and commitment therapy. Effects were generally of medium strength and had questionable clinical significance. When only the 8 studies targeting people with high PC were included, effects were larger and more consistent. Multimodal treatment showed the strongest effects when all studies were considered, whereas cognitive-behavioral therapy had the best evidence among targeted studies. Perspective: PC is a modifiable characteristic but most interventions produce only modest benefit unless targeted to people with high PC. More research into theory-driven interventions matched to specific patient profiles is required to improve treatment efficacy and efficiency.